2019
DOI: 10.3390/ijerph16112060
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat Preferentially Induces Apoptosis of Late Stage Effector Lymphocyte and Impairs Memory Immune Response in Mice

Abstract: Paraquat (PQ) is a toxic non-selective herbicide. To date, the effect of PQ on memory immune response is still unknown. We investigated the impact of PQ on memory immune response. Adult C57BL/6 mice were subcutaneously injected with 2 mg/kg PQ, 20 mg/kg PQ or vehicle control every three days for two weeks. A single injection of keyhole limpet hemocyanin (KLH) at day four after the initial PQ treatment was used to induce a primary immune response; a second KLH challenge was performed at three months post the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…ID: “treatment with 20 mg/kg PQ increased apoptosis of late stage effector cells to yield less memory cells and thereafter impair memory immune response,” [ 165 ]…”
Section: Commonality Of Contributing Factors Between Ibd and Id - Detailsmentioning
confidence: 99%
“…ID: “treatment with 20 mg/kg PQ increased apoptosis of late stage effector cells to yield less memory cells and thereafter impair memory immune response,” [ 165 ]…”
Section: Commonality Of Contributing Factors Between Ibd and Id - Detailsmentioning
confidence: 99%
“…Moreover, PQ impairs phagocytic activity of monocytes and granulocytes (Jang et al 2015), and induces apoptosis of mature CD4 T cells and B cells during a primary immune response. Thus, several studies mentioned above have shown that innate and adaptive immune cell functions were modulated after PQ exposure (Shao et al 2019). Likewise, PQ also has in uence on ROS production in human neural progenitor cells and increased lung malondialdehyde (MDA) level (Chang et al 2013;Toygar et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies suggested that PQ might increase the apoptosis of cells 4 , no increased apoptosis was observed in our study. It seems that various factors, including the dose of PQ and time of PQ exposure, may significantly influence the PQ effect 34 . The highest dose of PQ in our study was 20 mg/kg 35 , slightly higher than other studies 36 , but the mice in our study were injected with PQ only twice with 1 wk apart.…”
Section: Discussionmentioning
confidence: 99%